(untitled) (Revista Puertorriqueña de Psicologia, 2025)
Multicultural psychology has lost a significant paladin, defender, and guardian. Guillermo Bernal, a clinical psychologist, was a superb researcher, leader, clinician, teacher, collabo-rator, and mentor. As an immigrant, Latinx, and internationalist, Dr. Bernal infused his psychological work with a commitment to excellence. He provided superb contributions in his multiple roles. He was a friend, teacher, companion, professional, and leader. His leadership style was energetic, collaborative, and empowering. In fact, Dr. Bernal’s contri-butions helped to change psychology’s paradigm.